Aggressive cribriform‐morular variant of papillary thyroid carcinoma: Report of an unusual case with pulmonary metastasis displaying poorly differentiated features. Issue 12 (30th October 2018) - Tsuji, Hiromi; Yasuoka, Hironao; Nakamura, Yasushi; Hirokawa, Mitsuyoshi; Hiroshima, Takashi; Sakamaki, Yasushi; Miyauchi, Akira; Tsujimoto, Masahiko
Abstract : The cribriform‐morular variant of papillary thyroid carcinoma (CMV‐PTC) is a rare morphologic entity in which metastasis rarely occurs. Until now, only three cases of metastasis by CMV‐PTC have been reported. We present a rare sporadic case of CMV‐PTC with multiple lung metastases in a 28‐year‐old female, 3 years after total thyroidectomy. The lung tumor was not encapsulated but well‐circumscribed and showed a mixture of cribriform, papillary, and solid patterns of growth with necrosis. The tall columnar carcinoma cells did not display the typical nuclear features of PTC. Carcinoma cells were positive for thyroid transcription factor 1, paired‐box gene 8, estrogen receptor, progesterone receptor, and adenomatous polyposis coli, and showed positive nuclear and cytoplasmic staining for β‐catenin. Carcinoma cells were negative for thyroglobulin and CDX‐2, and the Ki‐67 labeling index was 22.1%. This immunoprofile suggests a pathological diagnosis of metastasis by a CMV‐PTC displaying poorly differentiated features. To the best of our knowledge, our case is the first report of CMV‐PTC with pulmonary metastasis that was confirmed by histological and immunohistochemical examinations. The present case suggests that CMV‐PTC with a high Ki‐67 labeling index may cause visceral metastasis.